Weather Conditions and Physical Activity: Insights for Climate Emergency Policies - Ignacio Belloc; José Ignacio Gimenez-Nadal; José Alberto Molina (Global Labor Organization (GLO), 2024)
This study explores the link between daily weather conditions and individual engagement in physical activities within the context of the climate emergency. Using ATUS data from 2003-2022, alongside detailed daily-county weather data, the research investigates their correlations. Results highlight a significant positive relationship between extreme high temperatures and heightened participation in physical activities, coupled with increased time dedicated to such pursuits. Surprisingly, individuals in warmer regions exhibit no adaptation to higher temperatures, contradicting initial assumptions. Furthermore, this study discerns sustained effects over a week, with additional hot days positively impacting physical activity within the preceding seven days. These findings hold crucial implications, shedding light on voluntary responses to global warming. They provide essential insights for formulating effective mitigation and adaptive policies aimed at promoting physical activity across varying weather conditions amid the ongoing climate emergency.
Keywords: I12; J22; Q54; 330; Physical activity; weather; extreme temperatures; health; time use; ATUS